Analisis kemampuan pemecahan masalah matematika aljabar berbasis timss pada siswa kelas viii Semester gasal SMP Negeri 1 Mojosongo Tahun 2015/2016 - Galih Mahanani, Linggar (2016)
Mathematic has an important position, because mathematic is basis of knowledge science which used widely in every part of life. The outcome of TIMSS (Trends in International Mathematics and Science Study) international assessment shows that mathematic problem solving in Indonesia are left behind another country. Analysis the ability of mathematical problem solving which more detail is needed to improve the mathematic achievement. This research aims to know the ability of mathematical problem solving algebra based on TIMSS and to find the percentage student's error. This research is a qualitative descriptive. The subjects of research were VIII F grade students of SMP Negeri 1 Mojosongo totaling 25 students. Data collection techniques used test, interview, observation, and documentation. Technique of analyzing data used included data reduction, data presentation, verification and conclusion drawing. The results obtained by the percentage of errors in the indicator to understand the problem 34.93%, planning problem solving 35.47%, carry out problem solving 53.6%, and checking back 60.8%. In term of the TIMSS cognitive domain percentage of errors in knowledge 52.8%, reasoning 69%, and application of 44%. In term of the problem-solving ability and cognitive domains in TIMSS shows that the error checking and reasoning more dominant than the other errors.